Late-manifestation of attention-deficit/hyperactivity disorder in older adults: an observational study - Hiroyuki Sasaki; Tadashi Jono; Ryuji Fukuhara; Kazuki Honda; Tomohisa Ishikawa; Shuken Boku; Minoru Takebayashi (BMC Psychiatry, 2022)
Abstract Background The age of attention-deficit/hyperactivity disorder onset is usually during the first 12 years of life; however, there have been recent reports of late-onset attention-deficit/hyperactivity disorder. These reports have been limited to that of young adults, and details in older adults remain unknown. As such, we had previously presented the first case report of “very” late-onset attention-deficit/hyperactivity disorder, wherein the symptoms presented in senile age. In this observational study, we aimed to investigate the prevalence and clinical features of such attention-deficit/hyperactivity disorders in older adults visiting our dementia clinic. Methods Four hundred forty-six consecutive patients visiting our specialty outpatient clinic for dementia during the 2-year period from April 1, 2015 to March 31, 2017 were included in this study. First, the patients were examined for the presence or absence of dementia in our specialty outpatient clinic for dementia. Those not diagnosed with dementia were examined for the presence or absence of attention-deficit/hyperactivity disorder in our specialty outpatient clinic for developmental disorders. Finally, these patients who were diagnosed with attention-deficit/hyperactivity disorder were investigated in detail to clarify their clinical characteristics. Results Of 446 patients (246 women and 200 men), 7 patients were finally diagnosed with attention-deficit/hyperactivity disorder. Although these 7 patients were initially suspected to have Alzheimer’s disease (considering their age, 6 of these 7 patients were suspected to have early onset Alzheimer’s disease), it was found that these symptoms were due to attention-deficit/hyperactivity disorder. These patients had four characteristics in common: (1) they were significantly younger than the complete study population; (2) they predominantly showed inattention-related symptoms; (3) they showed latent manifestation; and (4) they experienced a stressful life event before manifestation. Conclusions Our previous case report suggested that very late-onset attention-deficit/hyperactivity disorder patients could be incorrectly diagnosed with dementia. In this observational study, 1.6% of patients who were initially suspected of having dementia were actually diagnosed with attention-deficit/hyperactivity disorder. This study also showed that the “late-onset” described in our previous report would be better described as “late-manifestation.” A clinician should consider late-manifestation of attention-deficit/hyperactivity disorder in the differential diagnosis when encountering dementia patients, especially early onset Alzheimer’s disease.